Descriptive Study on Skin Prick Test in Allergy Clinic Immanuel Hospital Bandung Indonesia - Garna, Danny R; Lucianus, Johan; Ivone, July (Maranatha Christian University, 2017)
Allergy is a change of reaction or bodys defense response to substances that are actually harmless. An estimated 10-20% of the population had been or are suffering from the disease. The purpose of this study was to thoroughly observe allergic patients on Allergy Clinic Immanuel Hospital Bandung from January 2013âJanuary 2014 based on allergen, clinical sign, age and gender. This study use descriptive methods with retrospective data retrieval from medical record. We gathered 206 skin prick test (SPT) results and found that the highest incidence of allergy was between 31-40 years (22.33%), 64.54% were women, 43.20% of patients with dermatitis as the major clinical signs, 70.59% of patients allergic to house dust mite as a common environmental allergens, 24.84% of patients allergic to shrimp as the most common food allergens. In conlusion, allergic patients with SPT positive common at the age of 31-40 years, women, Dermatitis as a major clinical signs. The most common environmental allergens that cause allergy was house dust mite. The most common food allergens that cause allergy was shrimp.Keywords: allergy, dermatitis, Immanuel Hospital Bandung, skin prick test